THE SPECIFICITY, INVESTMENT EVALUATION AND EFFICIENT USE OF AVAILABLE ENTERPRISE RESOURCES - Natalia Nikolaevna Novoselova (Современная наука и инновации)
In this article the purpose of own capital audit is considered, the main check directions of this type audit, and also recommended auditor procedures of joint-stock company own capital check.